Absolute Configuration of Resveratrol Oligomers Isolated from Hopea utilis. Issue 1 (January 2015) - Ito, Tetsuro; Hoshino, Ryosuke; Iinuma, Munekazu
Abstract Phytochemical studies on a stem of Hopea utilis (Dipterocarpaceae) resulted in the isolation of two new resveratrol derivatives, namely hopeaside E (1; resveratrol trimer) and hopeaside F (2; resveratrol pentamer), together with ten known resveratrol derivatives, 3–12. The structures of the new compounds were elucidated by spectroscopic analyses, including NMR experiments, and their absolute configurations were determined on the basis of a comparative configurational analysis using the β‐D‐glucopyranosyl group and chiroptical data. The absolute configuration of (+)‐balanocarpol (3) was also determined by acid‐catalyzed skeletal conversion.